(untitled) (Bangladesh Journal of Otorhinolaryngology, 2015)
This cross sectional study with purposive sampling based on 50 cases of solitary thyroid nodule and multi-nodular goitre for operation in department of Otolaryngology and Head-Neck surgery of SSMC & Mitford Hospital, Dhaka and Dhaka Medical college, Dhaka during January 2009 to December 2009. Objectives of this study to find out relative frequency of malignancy in solitary thyroid nodule and multi-nodular goitre (by histopathology). Each case was studied by history taking, physical examination and relevant investigations. In this series, male to female ratio was 1:7. Mean age of the patients of nodular goitre was 36.5+12.33 years and the highest number of patients were found in age group 31-40 years. After operation, histopatholoical report analysis was done and found that nodular colloidal goitre was 52%, follicular adenoma was 24% and auto-immune thyroiditis was 6%. Among the malignancies papillary carcinoma was 66.66%, follicular carcinoma was 22.22% and anaplastic carcinoma was 11.11%. The relative frequency of malignancy in solitary thyroid nodule was 28% and in multi-nodular goitre was 8%. As there is a chance of malignancy is high so it should get serious medical attention DOI: http://dx.doi.org/10.3329/bjo.v20i2.22019 Bangladesh J Otorhinolaryngol; October 2014; 20(2): 55-59